Analisis Nilai Wajar Sewa Tanah Pada Pusat Latihan Tempur Marinir Grati Pasuruan - Murtaji, Murtaji (JURNAL AKUNTANSI DAN MANAJEMEN MUTIARA MADANI, 2024)
. The utilization of state asset, such as land, which is not used for the organizational tasks and functions is very important. This study aims to analyze the fair value of land rent at the Grati Pasuruan Marine Tempur Training Center. The research sample was determined using a purposive sampling technique. This study analyzed the fair value of land rent of 219,604 square meters for a lease period of 5 (five) years. The analysis was carried out using an income approach with a discounted cash flow method. The market data comparison method produced a fair value of land of Rp44,488,329,000 or Rp202,584.22 per square meter. The discounted cash flow analysis used the assumption of a cost of capital of 7.39 percent calculated using the Capital Asset Pricing Model (CAPM), a cost of debt of 9.29 percent, with a risk-free rate of return of 6.805 percent, a beta of 0.745, a market risk of 7.38 percent, a discount rate of 7.99 percent and a growth rate of 2.51 percent. The fair value of land rent for 5 (five) years is IDR 11,046,292,000 with a lump sum payment up front.